International Association of Dental Traumatology guidelines for the management of traumatic dental injuries: 1. Fractures and luxations. Issue 4 (17th July 2020) - Bourguignon, Cecilia; Cohenca, Nestor; Lauridsen, Eva; Flores, Marie Therese; O'Connell, Anne C.; Day, Peter F.; Tsilingaridis, Georgios; Abbott, Paul V.; Fouad, Ashraf F.; Hicks, Lamar; Andreasen, Jens Ove; Cehreli, Zafer C.; et al.
Abstract: Traumatic dental injuries (TDIs) of permanent teeth occur frequently in children and young adults. Crown fractures and luxations of these teeth are the most commonly occurring of all dental injuries. Proper diagnosis, treatment planning, and follow up are important for achieving a favorable outcome. Guidelines should assist dentists and patients in decision making and in providing the best care possible, both effectively and efficiently. The International Association of Dental Traumatology (IADT) has developed these Guidelines as a consensus statement after a comprehensive review of the dental literature and working group discussions. Experienced researchers and clinicians from various specialties and the general dentistry community were included in the working group. In cases where the published data did not appear conclusive, recommendations were based on the consensus opinions of the working group. They were then reviewed and approved by the members of the IADT Board of Directors. These Guidelines represent the best current evidence based on literature search and expert opinion. The primary goal of these Guidelines is to delineate an approach for the immediate or urgent care of TDIs. In this first article, the IADT Guidelines cover the management of fractures and luxations of permanent teeth. The IADT does not, and cannot, guarantee favorable outcomes from adherence to the Guidelines. However, the IADT believes that their application can maximize the probability of favorable outcomes.